Critical phosphorus levels of Brachiaria decumbens (Stapf) Prain, Brachiaria humidicola (Rendle) Schweickerdt, Digitaria decumbens Stent, Htpharrhenia rufa (Ness) Stapf, Melinis minutiflora Pal de Beauv, Panicum maximum Jacq., and Pennisetum purpureum Schum - Martinez, H.E.P.; Haag, H.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
Seven tropical grass species were cultivated in nutrient solutions added the following amounts of phosphorus in mg./ 1.: 0.12, 0.48, 1.94, 7.75, 31.00. 75 days later, the plants were harvested and divided into: leaves, stems, scheaths and roots. The material was dried at 1789F, wheighed analysed for phosphorus by the conventional colometric method. The data were submited to statistical treatement and interpretation. The authors concluded: 1. Differential phosphorus responses among the grasses, were observed. B. humidicola and H. rufa showed the lowest external phosphorus requirements, followed by B. decumbens, M. minutiflora, P. maximum, P. purpureum, and D. decumbens. 2. Differential phosphorus contents were observed among the species. The highest internal phosphorus requirement was observed for D. decumbens (0.38%) followed by B. decumbens (0.32%), B. humidicola (0.26%), M. minutiflora (0.24%), P. maximum (0.24%), P. purpureum (0.20%). 3. The best absorption capacity and utilization of phosphorus was observed for B. humidicola followed by P. purpureum, P. maximum. D. decumbens, B. decumbens, and M. minutiflora.